Pengaruh Waktu Iradiasi Ultrasonik dengan Aktivasi Kalium Hidroksida terhadap Sifat Fisis Karbon Aktif dari Serbuk Karet End Life Tire - Arifin, Uma Fadzilia; Adetya, Nais Pinta; Pambudi, Wisnu; Listyalina, Latifah; Ratnaningsih, Wahyu (Jurnal Teknik Kimia USU, 2024)
Processing End Life Tire (ELT) rubber powder into activated carbon is an alternative for handling tire waste. One way to improve physical properties such as proximate characteristics, surface area and pore diameter of activated carbon is through chemical activation assisted by ultrasonic irradiation. This research aims to determine the effect of ultrasonic irradiation time with potassium hydroxide (KOH) activation on the quality of ELT rubber activated carbon. Activated carbon was synthesized and activated using 30% KOH at various ultrasonic irradiation times, namely 0 minutes, 15 minutes, 30 minutes, 45 minutes and 60 minutes. Based on the characterization results, activated carbon with an ultrasonic irradiation time of 30 minutes is the active carbon that has the most superior properties. The proximate characteristics of activated carbon meet the active carbon quality requirements of SNI 06–3730–1995 and have the highest surface area, namely 401.11 m2/g and pore diameter of 2.1652 nm, which is included in the mesoporous structure category so that it has the potential to be applied as an adsorbent for heavy metals from contaminated fluid.